Improving models for sustainability evaluation of construction projects in the initiation and planning processes - Fesenko, T. (My University, 2022)
The object of this study is the management processes of «sustainable construction». Sustainability is considered through the application of management processes that, in addition to the traditional tasks for construction projects, also outline the tasks of a wider context. Strategies and production practices of «sustainable construction» involve taking into account environmental, social and economic factors that affect a wide range of stakeholders and the overall condition of the built space. In this regard, the issue of applying management processes in the construction industry that ensure proper organizational and technological sustainability of projects is also being updated. This article aims to fill the existing information and methodological gap in the processes of assessing the sustainability of construction project management processes. A correlation method was applied to determine the interdependencies of the characteristics of the use of tools and methods in the processes of managing construction projects with the values of sustainable development 5Р (Product, Proses, People, Planet, and Prosperity). Highlighting the characteristics of permanence in project management processes helps to explain the difference in approaches for ensuring the internal sustainability of the construction object and the sustainable management of a construction project. A comprehensive methodology for quantitative assessment of sustainable construction project management in the initiation and planning processes under conditions of uncertainty is proposed. The relative importance of construction project management processes and subcategories of sustainable development of the construction site is taken into account. Basic mathematical models of sustainability assessment have been developed: balanced in all areas of nowledge of construction project management for each process, balanced cross all construction project management processes at the «Initiation» and «Planning» phases for each category of sustainable development, and integral assessment of sustainability of construction project management processes
Keywords: project management; construction project; sustainability; sustainable development; planning processes